2016
DOI: 10.1016/j.neuron.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of NRP1 in Axon Guidance and Subcellular Target Recognition in Cerebellum

Abstract: Subcellular target recognition in the CNS is the culmination of a multiple-step program including axon guidance, target recognition, and synaptogenesis. In cerebellum, basket cells (BCs) innervate the soma and axon initial segment (AIS) of Purkinje cells (PCs) to form the pinceau synapse, but the underlying mechanisms remain incompletely understood. Here, we demonstrate that neuropilin-1 (NRP1), a Semaphorin receptor expressed in BCs, controls both axonal guidance and subcellular target recognition. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 45 publications
2
64
0
Order By: Relevance
“…In the present study we further show that Sema3A and NRP1 are the main molecular cues that coordinate AIS innervation by controlling both BC axons pathfinding and subcellular target recognition [4]. In particular, NRP1 expressed in BC axons plays the role of matchmaker or facilitator, first by bringing the pre- and post-synaptic elements in close proximity and second by sealing their physical interaction through a direct binding with the post-synaptic molecule NF186.…”
supporting
confidence: 60%
“…In the present study we further show that Sema3A and NRP1 are the main molecular cues that coordinate AIS innervation by controlling both BC axons pathfinding and subcellular target recognition [4]. In particular, NRP1 expressed in BC axons plays the role of matchmaker or facilitator, first by bringing the pre- and post-synaptic elements in close proximity and second by sealing their physical interaction through a direct binding with the post-synaptic molecule NF186.…”
supporting
confidence: 60%
“…For example, a number of the transcripts that were upregulated in SOD1 G93A axons appear detrimental, including; Adgr1, which can induce apoptosis and cause reduction in neurite outgrowth (Zuko et al, 2016). Furthermore, multiple transcripts that are important for axon function were downregulated or absent in SOD1 G93A axons, including; Dbn1 which is important for axon initiation, growth and guidance, (Lin and Koleske, 2010;McIntyre et al, 2010;Sharma et al, 2012), Nrp1 (Neuropilin 1) which is a semaphorin receptor involved in both axon guidance and subcellular target recognition (Telley et al, 2016); and Mgrn1 a ubiquitin-ligase, which appears important for mitochondrial function and neuronal survival .…”
Section: Discussionmentioning
confidence: 99%
“…5E). For instance, we found that several transcripts paramount for proper axon function were downregulated or completely absent in SOD1 G93A axons, including Dbn1 (Lin and Koleske, 2010;McIntyre et al, 2010;Sharma et al, 2012), Nrp1 (neuropilin 1) (Telley et al, 2016) and Mgrn1 . Some transcripts that were upregulated in SOD1 G93A axons appear detrimental, including Adgr1 (Zuko et al, 2016) (Fig.…”
Section: The Als-causative Mutation Sod1 G93a Modulates the Axonal Trmentioning
confidence: 97%
“…Our results also extend current knowledge that axon guidance genes can undergo alternative splicing in MB tumors (Dubuc et al ., ). Interestingly, several differentially expressed SEMA genes such as SEMA6A (Renaud et al ., ), PLXNA2 (Renaud et al ., ), NRP1 (Telley et al ., ), and L1CAM (Huang et al ., ) have been shown to play a role in cerebellar development further underscoring the notion that an early cerebellar stem/progenitor is the cell of origin for Group 3 and Group 4 MB. Indeed, a large number of neuronal differentiation genes (Table ) including, but not limited to, CBLN1 , NEUROD1 , NR2F1 , and NRXN1 (Schuller et al ., ; Uemura et al ., ) have been implicated in cerebellar morphology and/or granule cell development thus further validating the biological relevance of the tumorsphere model system.…”
Section: Discussionmentioning
confidence: 99%